Stress-activated kinases signaling pathways in cancer development. Issue 19 (February 2021) - Herrera-Melle, Leticia; Crespo, María; Leiva, Magdalena; Sabio, Guadalupe
Abstract : Cancer is a large group of diseases characterized by abnormal cell growth that can lead to metastasis. It is the second leading cause of death worldwide, and its incidence is expected to rise over the next decades. Stress-activated protein kinases (SAPK) are important players in its regulation. Several studies have tried to unravel their role; however, their pro-tumorigenic or anti-tumorigenic properties are sometimes controversial. In this review, we will discuss the main roles of the different SAPK in the control of tumor development through essential processes such as cell proliferation, apoptosis or invasiveness. We will also show the latest discoveries regarding the contribution of SAPK in shaping tumor microenvironment through the regulation of organ crosstalk and immune cell response during cancer progression. All these studies are relevant examples of how SAPK offer new therapeutic avenues for cancer patients that may help increase their survival.